Psychophysical therapy and underlying neuroendocrine mechanisms for the rehabilitation of long COVID-19 - Meng, Qing-Tai; Song, Wu-Qi; Churilov, Leonid P.; Zhang, Feng-Min; Wang, Yu-Feng (Frontiers in Endocrinology, 2023)
With the global epidemic and prevention of the COVID-19, long COVID-19 sequelae and its comprehensive prevention have attracted widespread attention. Long COVID-19 sequelae refer to that three months after acute COVID-19, the test of SARS-CoV-2 is negative, but some symptoms still exist, such as cough, prolonged dyspnea and fatigue, shortness of breath, palpitations, insomnia. Its pathological mechanism is related to direct viral damage, immunopathological response, endocrine and metabolism disorders. Although there are more effective methods for treating COVID-19, the treatment options available for patients with long COVID-19 remain inadequate. Psychophysical, such as exercise, oxygen therapy, photobiomodulation, and meditation, have been attempted as treatment modalities for long COVID-19, and studies have confirmed their potential to promote recovery through immune regulation, antioxidant effects, and neuroendocrine regulation. Neuroendocrine regulation plays a significant role in repairing damage after viral infection, regulating immune homeostasis, and improving metabolic activity, in patients with long COVID-19. As a result, this review uses oxytocin as an example to examine the neuroendocrine mechanisms involved in the psychophysical of long COVID-19 syndrome and proposes a psychophysical strategy for the treatment of long COVID-19.